The Influence of Promotion, E-Wom and Trust on Purchasing Decisions on E-Commerce Lazada in Batam City - Shellen, Shellen; Husein, Alice Erni (Transpublika Publisher, 2025)
The primary objective of this investigation is to examine how promotion, electronic word of mouth (e-WOM), and trust impact buying choices on Lazada e-commerce in Batam City. This quantitative study used a replication approach and statistical methods to analyse primary data obtained from 100 participants through online questionnaires, sampled using non-probability techniques based on specific criteria. Utilising the SPSS application, the data was analysed to determine the impact of the independent variables on the dependent variable. The results indicated that promotion, e-WOM, and trust individually have a favourable and significant effect on buying decisions. Furthermore, these three factors collectively have a notable impact on purchasing decisions on Lazada e-commerce. The outcomes suggest that successful promotional strategies, positive feedback from consumers, and consumer trust are critical factors influencing purchasing decisions on e-commerce platforms. Based on these results, researchers suggest that Lazada increase the frequency of promotional campaigns such as Harbolnas or flash sales, provide incentives for consumers to leave product reviews, and strengthen consumer trust through guarantees of product authenticity and transparency of payment security systems. This strategy is expected to strengthen consumer trust and increase purchasing decisions on the Lazada platform.